Kinship Relations between the Founder of Muhammadiyah and the Founder of NU: Analysis of the Breed Lineage of Sultan Hadiwijaya - Abidin, Zainul; Liza, Fitri; Fahmi, Ari Khairurrijal (JURNAL ISLAM NUSANTARA, 2023)
The focus of this research is to identify the genealogy of the two founders, namely the founder of Muhammadiyah and the founder of NU, who are related to Sultan Hadiwijaya. This study aims to find out the genealogy of the two founders to Sultan Hadiwijaya and reveal their kinship. The method used in this study is a qualitative method using a historical approach. Primary data sources are obtained from literature on the genealogy of the founder of Muhammadiyah and the founder of NU. Secondary data sources are obtained from other literature relevant to the research problem. The data analysis method is descriptive-genealogy analysis by describing the genealogy of the founder of Muhammadiyah and the founder of NU through the breedage of Sultan Hadiwijaya and analyzing their kinship. The results showed that the two founders were cousins of the lineage of Sultan Hadiwijaya. The existence of family relations between the two figures is expected to strengthen the brotherhood of Muhammadiyah and NU citizens. The implication of this research is that an understanding of the kinship between the founder of Muhammadiyah and the founder of NU with Sultan Hadiwijaya can strengthen cooperation between the two organizations as well as strengthen brotherhood among its members, which in turn can enrich our insight into the history and dynamics of Islam in Indonesia.